Julius Caesar's Battle for Gaul : new archaeological perspectives - Fitzpatrick, Andrew P.; Haselgrove, Colin (Oxbow Books, 2019)
Between 58 and 51 BC Julius Caesar conquered Gaul. He campaigned across much of present day France and the Low Countries, crossed the Rhine to Germany, and sailed the Channel to invade Britain. In doing this he achieved immense personal wealth and glory and the loyalty of a battle-hardened army of veterans. Caesar's eventual return to Rome began with the crossing of the Rubicon which started a bloody civil war from which he emerged victorious and as dictator.0Roman historians have little to say on the consequences of the war on the Iron Age communities of north-west Europe. Their story is told instead by archaeology and numismatics. Huge numbers were involved in the war, at a vast cost in people and wealth. In the aftermath, leaders sympathetic to Rome were installed and sometimes whole peoples were resettled. The diplomatic relations created at this time directly affected the eventual incorporation of these peoples into the Roman Empire.0This book presents the latest archaeological research on the Battle for Gaul and its aftermath. Based on an acclaimed 2017 conference, it is the first Europe-wide overview and much of the research is published here in English for the first time. After an introduction to recent trends in historical studies, thematic studies and regional surveys analyse the archaeological and numismatic evidence from across north-west Europe. Comparative evidence for the Roman conquest of Spain is also examined, along with the fundamental role that the study of the Battle for Gaul played in shaping the development of Iron Age archaeology